AMIR TEMUR AND PERIOD OF THE TEMURIDS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Amir Temur, known in the West as Tamerlane, was a 14th-century conqueror whose military prowess and administrative acumen established the vast Temurid Empire, stretching from the Middle East to India and from Russia to China. Born in 1336 near Samarkand, Temur rose to power by consolidating Transoxiana and embarked on extensive military campaigns that reshaped the political landscape of Asia. Despite his reputation for brutality, Temur was a patron of culture and the arts, transforming Samarkand into a cultural and intellectual hub. His architectural commissions, such as the Bibi-Khanym Mosque and the Gur-e Amir mausoleum, exemplify the era's artistic achievements. The Temurid Renaissance, particularly under his grandson Ulugh Beg, saw significant advancements in science, literature, and the arts, blending Persian, Mongol, and Turkish influences into a unique cultural synthesis. This period represents a golden age in Central Asian history, marked by remarkable contributions to art and science, solidifying Temur's dual legacy as both a conqueror and a cultural patron.